Physico-mechanical properties of super-fast dried oil palm lumber as the core of block board - Wong, Zhi Shan (2017)
Super-Fast Drying is a new, efficient technology used to dry oil palm wood by creating minimum drying defects. However, holed appearance on the lumber deducts its economic value. Therefore, block board was suggested to increase the value of super-fast dried lumber. The lumbers worked as the core of block board and laminated with thin Keruing veneers as the surface layers. The possibility of block board as the end product of super-fast dried lumbers was investigated in this project by using high density and low density super-fast dried lumbers. Besides, the physical and mechanical properties of the block board were determined. In the beginning, the core lumbers were holed according to optimum diameter and distance between two holes. Then, 2-step drying was carried out, hot-press drying came first and high temperature kiln drying came then. After one-week conditioning, the lumbers were then further process by butt jointing two lumbers together between two veneers. The sandwich structure was then hot-pressed to cure the resin. Two stoppers were put on the sides to achieve target final thickness of block boards. After one-week conditioning, block boards were cut for testing. The results confirmed the availability of block board as the end product of super-fast dried lumbers. There was significant difference between block board made with untreated oil palm lumber and super-fast dried oil palm lumber as the core in MOE, while for physical properties, there was different between both samples after 2-hour immersion in water. Besides, the block boards made of super-fast dried lumbers showed minimum drying defect.